2013
DOI: 10.1080/09712119.2013.823863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of glutamine and mannan oligosaccharides on plasma endotoxin and acute phase protein concentrations and nutrient digestibility in finishing steers

Abstract: This study was conducted to investigate the effects of dietary supplementation of glutamine (Gln) and mannan oligosaccharides (MOS) on plasma endotoxin and acute phase protein concentrations and nutrient apparent digestibility in finishing steers. Eighteen Simmental )Luxi crossbred finishing steers were randomly and evenly divided into three treatments: (1) the basal diet (control); (2) the basal diet ' 1% Gln; (3) the basal diet ' 0.2% MOS. The results showed: dietary supplementation of Gln decreased the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These findings are consistent with various other reports which found that MOS could increase the digestibility and retention rate of There are fewer studies in ruminants, and the results are less conclusive. For example, MOS did not affect apparent nutrient digestibility in steers (Jin et al, 2014), and yeast culture did not alter apparent nutrient digestibility in dairy heifers (Lascano and Heinrichs, 2009), dairy cows (Moallem et al, 2009), steers (Hinman et al, 1998), or lambs (Adams et al, 1981. In addition, Holstein cows given diet containing 56 g•d −1 of yeast culture showed only a small numerical increase in NDF digestibility (White et al, 2008).…”
Section: Nutrient Apparent Digestibility and Retention Ratementioning
confidence: 99%
“…These findings are consistent with various other reports which found that MOS could increase the digestibility and retention rate of There are fewer studies in ruminants, and the results are less conclusive. For example, MOS did not affect apparent nutrient digestibility in steers (Jin et al, 2014), and yeast culture did not alter apparent nutrient digestibility in dairy heifers (Lascano and Heinrichs, 2009), dairy cows (Moallem et al, 2009), steers (Hinman et al, 1998), or lambs (Adams et al, 1981. In addition, Holstein cows given diet containing 56 g•d −1 of yeast culture showed only a small numerical increase in NDF digestibility (White et al, 2008).…”
Section: Nutrient Apparent Digestibility and Retention Ratementioning
confidence: 99%
“…Supplementation of 12 Lactobacillus strains decreased colonization of three strains of E. coli in the GIT and up to five strains of Salmonella enterica spp. This is potentially due to the capacity of Lactobacillus species to adhere strongly to the small intestinal mucosa and epithelium and produce substances to decrease pathogenic growth (Jin et al, 2014). Other potential mechanisms of action include maintenance of host microbial communities and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that Gln has anti-inflammatory and antioxidative effects in lactating cows. For example, as reported for finishing steers [ 136 ], the intravenous infusions of 106 and 212 g Gln/day increased the concentrations of LPS-binding protein in the plasma of lactating cows [ 70 ]. Cows infused with 106 g Gln/day had greater concentrations of the serum amyloid A (an acute phase protein) in plasma on days 14 (+108%) and 21 (+106%) postpartum, compared with controls.…”
Section: Glu and Gln Nutrition In Ruminantsmentioning
confidence: 99%
“…At present, the National Research Council (NRC) has not established dietary requirements for preruminants or ruminants (e.g., calves, beef cattle, dairy cows, lambs, and ewes) for Glu or Gln [ 75 , 121 ]. However, there is evidence that preruminants, as well as adult sheep, goats, dairy cows, and cattle, require dietary Glu ( Table 5 ) and Gln ( Table 6 ) supplementation for maximal growth and production performance, as well as for optimal (particularly intestinal) health and function, as detailed in the following sections [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ]. This represents a paradigm shift in ruminant nutrition.…”
Section: Glu and Gln Nutrition In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation